Comparison of tri-, tetra- and pentacyclic caged hydrocarbons in Australian crude oils and condensates - Scarlett, Alan; Spaak, G.; Mohamed, S.; Plet, Chloe; Grice, Kliti (Pergamon, 2019)
Thermally stable and biodegradation resistant, the tricyclic and pentacyclic diamondoid caged hydrocarbons are commonly used as source and maturity indicators of oils and potential source-rocks, but similar tetracyclic structures appear to have received much less attention. Using two-dimensional (2D) gas chromatography – time of flight mass spectrometry (GC × GC-TOFMS), 29 Australian crude oils and condensates were analysed for the presence of caged C12H18 tetracyclics such as ethanoadamantane and iceane. The thermodynamically more stable 2,4-ethanoadamantane was identified by comparison with a synthesised authentic standard. Three of its bridgehead methyl-substituted isomers, 6-methylethanoadamantane (6-ME), 1-ME and 2-ME, were tentatively assigned based on mass spectral comparison and relative elution order. Further series of non-bridgehead methyl isomers, plus dimethyl isomers, were also inferred based on mass spectra and 2D elution positions. The tri-, tetra and pentacyclic caged hydrocarbons and their methyl-substituted homologues were semi-quantified in the Australian oils. The potential of a novel index, the methylethanoadamantane index (MEI), based on the ratio of the more stable bridgehead isomers divided by the sum of all the methyl substituted isomers (MEI = S(6-ME + 1-ME + 2-ME)/STotal methylethanoadamantanes), was explored. A significant positive association was found between the MEI and MAI (r2 = 0.203, p < 0.05) and a significant negative association was found between MEI and MDI (r2 = 0.246, p < 0.05). Stronger relationships were found for other commonly applied diamondoid ratio indices, including S Methyl Adamantanes/S Methyl Diamantanes (SMA/SMD) versus SMA/SME (r2 = 0.781, p < 0.0001, n = 26). The relatively low volatility of the ethanoadamantanes compared to the adamantanes and their likely greater resistance to microbial attack than the ethyladamantanes, may make analysis of these compounds a useful addition to the commonly measured diamondoids.